Sports massage therapy on the reduction of delayed onset muscle soreness: A systematic review and meta analysis - Dhiva Luhtirani Yanitamara; Suryo Saputra Perdana; Amalia Nur Azizah (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: DOMS (Delayed Onset Muscle Soreness) is a condition where muscle pain appears shortly after activity, usually occurring shortly after doing sports or activities that exceed the usual capacity. It can also be caused by doing sports or activities he has never done before. DOMS usually appears in a healthy person but mainly occurs in athletes. A sports massage intervention is recommended to reduce the DOMS in the recovery process.Purpose: To determine whether sports massage can reduce DOMS and provide recovery effects on a person.Method: This research is a systematic review and meta-analysis using the PRISMA diagram. Performed article search with eligibility test with PICO. Population: people with DOMS. Intervention: Sport massage. Comparison: control treatment. Outcome: pain reduction. The articles used came from 2 databases, namely PubMed and Science Direct. The keywords in this article search are